2014
DOI: 10.4103/0972-0707.139833
|View full text |Cite
|
Sign up to set email alerts
|

Viability and antibacterial efficacy of four root canal disinfection techniques evaluated using confocal laser scanning microscopy

Abstract: Background:Several disinfection techniques have been recently introduced with the main objective of improving root canal disinfection in the inaccessible areas of the root canal system. This in vitro study was done to evaluate the antimicrobial effect and viability of Enterococcus faecalis biofilms using conventional irrigation, EndoActivator (Dentsply, Tulsa Dental, USA), diode laser irradiation and photon-initiated photoacoustic streaming (PIPS).Materials and Methods:Root canals of 130 single rooted mandibul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 24 publications
(30 reference statements)
1
13
0
Order By: Relevance
“…The results are in accordance with the study done by Mathew et al , to evaluate antimicrobial efficacy where EndoActivator showed better results (1.79 ± 0.21 × 10 6 CFU/ml) than conventional needle irrigation (2.45 ± 0.22 × 10 6 CFU/ml). [ 9 ] This was also confirmed in the study where significantly greater efficiency of the EndoActivator against intracanal Enterococcus faecalis biofilm compared to the NaOCl irrigation alone was found. [ 10 ] Similar bacterial load reduction was reported by Pasqualini et al , (2010).…”
Section: Discussionsupporting
confidence: 53%
“…The results are in accordance with the study done by Mathew et al , to evaluate antimicrobial efficacy where EndoActivator showed better results (1.79 ± 0.21 × 10 6 CFU/ml) than conventional needle irrigation (2.45 ± 0.22 × 10 6 CFU/ml). [ 9 ] This was also confirmed in the study where significantly greater efficiency of the EndoActivator against intracanal Enterococcus faecalis biofilm compared to the NaOCl irrigation alone was found. [ 10 ] Similar bacterial load reduction was reported by Pasqualini et al , (2010).…”
Section: Discussionsupporting
confidence: 53%
“…Clinical and in vitro studies show controversial results regarding the priority of sonic irrigation systems rather than routine syringe irrigation. 26 , 27 , 28 , 29 To the best of our knowledge, this is the first study evaluating the use of a sonic activation system in root canal irrigation of primary teeth and it was shown that activation with sonic devices would not significantly improve removal of the bacteria from the root canal systems of primary teeth. However, it should be considered that the current study was performed on single-rooted teeth.…”
Section: Discussionmentioning
confidence: 91%
“…However, it is unlikely to remove microorganisms completely because of the complex anatomy of the canal system such as fins, isthmuses, lateral canals, apical deltas, etc. 8 Therefore, persistence of intracanal bacteria is believed to be one of the most common causes of endodontic treatment failure. 9 …”
Section: Introductionmentioning
confidence: 99%